Can endoscopic ultrasonography (EUS) improve the accuracy of clinical T staging by computed tomography (CT) for gastric cancer?. Issue 8 (August 2021) - Lee, Kyung-Goo; Shin, Cheong-Il; Kim, Sang Gyun; Choi, Jeongmin; Oh, Seung-Young; Son, Young-Gil; Suh, Yun-Suhk; Kong, Seong-Ho; Lee, Hyuk-Joon; Kim, Se Hyung; Lee, Kuhn Uk; Kim, Woo Ho; et al.
Abstract: Introduction: With the introduction of new therapeutic options for gastric cancer treatment, more precise preoperative staging of gastric cancer is needed. The purpose of this study was to evaluate the role of endoscopic ultrasonography (EUS) for improving the accuracy of clinical T staging by computed tomography (CT) for gastric cancer. Materials and methods: A total of 2636 patients underwent stomach protocol CT (S-CT) and EUS, followed by gastrectomy for primary gastric adenocarcinoma between September 2012 and February 2018 at Seoul National University Hospital. The results of preoperative S-CT and EUS were compared to the postoperative pathologic staging. Results: The overall accuracy of S-CT and EUS for T staging were 69.4% and 70.4%, respectively. When T staging was divided into T1-2 and T3-4 for clinically advanced gastric cancer (AGC), the positive predictive value for T3-4 using S-CT, EUS, and a combination of both modalities was 73.8%, 79.3%, and 85.6%, respectively. In 114 cases of indeterminate lesions between cT1 and cT2 by S-CT, EUS had a better prediction rate than the final decision based on endoscopy or the agreement between the two experts (Match rate: EUS vs. final decision, 69.3% vs. 58.8%). Conclusion: EUS can be a complementary diagnostic tool to clinical T staging of gastric cancer by CT for selecting T3-4 lesion.